'Transitions are Scary for our Kids, and They're Scary for us': Family Member and Youth Perspectives on the Challenges of Transitioning to Adulthood with Autism. Issue 6 (5th March 2015) - Cheak‐Zamora, Nancy C.; Teti, Michelle; First, Jennifer
<x xml:space="preserve">Abstract</x> Background Adolescents with autism spectrum disorder (ASD) face many challenges as they age into adulthood. Because little is known about the perspectives of caregivers and youth during this critical transition, this study explored their social, educational, and vocational needs and experiences. Method Two focus groups were conducted with youth with ASD (n = 13) and two focus groups were conducted with their caregivers (n = 19), where theme analysis strategies derived from Grounded Theory were utilized to identify themes. Results Both groups experienced fear and anxiety about transitioning, unmet needs were also high, leaving caregivers struggling to fill gaps. Most caregivers and youth reported lacking individualized services. Caregivers faced difficulty in motivating youth and creating opportunities for education and employment. Although youth have future goals, they were unaware of steps needed to accomplish them and hesitant to talk to caregivers. Conclusions Findings indicate considerable unmet needs for caregivers and youth with ASD. Perspectives of both groups should be considered when developing programmes and educating providers.